Enhanced anticancer activity of a combination of docetaxel and Aneustat (OMN54) in a patient‐derived, advanced prostate cancer tissue xenograft model. Issue 2 (15th December 2013) - Qu, Sifeng; Wang, Kendric; Xue, Hui; Wang, Yuwei; Wu, Rebecca; Liu, Chengfei; Gao, Allen C.; Gout, Peter W.; Collins, Colin C.; Wang, Yuzhuo
Abstract : The current first‐line treatment for advanced metastatic prostate cancer, i.e. docetaxel‐based therapy, is only marginally effective. The aim of the present study was to determine whether such therapy can be improved by combining docetaxel with Aneustat (OMN54), a multivalent botanical drug candidate shown to have anti‐prostate cancer activity in preliminary in vitro experiments, which is currently undergoing a Phase‐I Clinical Trial. Human metastatic, androgen‐independent C4‐2 prostate cancer cells and NOD‐SCID mice bearing PTEN‐deficient, metastatic and PSA‐secreting, patient‐derived subrenal capsule LTL‐313H prostate cancer tissue xenografts were treated with docetaxel and Aneustat, alone and in combination. In vitro, Aneustat markedly inhibited C4‐2 cell replication in a dose‐dependent manner. When Aneustat was combined with docetaxel, the growth inhibitions of the drugs were essentially additive. In vivo, however, the combination of docetaxel and Aneustat enhanced anti‐tumor activity synergistically and very markedly, without inducing major host toxicity. Complete growth inhibition and shrinkage of the xenografts could be obtained with the combined drugs as distinct from the drugs on their own. Analysis of the gene expression of the xenografts using microarray indicated that docetaxel + Aneustat led to expanded anticancer activity, in particular to targeting of cancer hallmarks that were not affected by the single drugs. Our findings, obtained with a highly clinically relevant prostate cancer model, suggest, for the first time, that docetaxel‐based therapy of advanced human prostate cancer may be improved by combining docetaxel with Aneustat. Highlights: First‐line, docetaxel‐based therapy of advanced prostate cancer is only marginally effective. The efficacy of docetaxel combined with Aneustat was determined in a metastatic xenograft model. Anti‐tumor activity was synergistically and markedly enhanced without major host toxicity. Gene expression analysis indicated docetaxel + Aneustat led to expanded anticancer activity. Docetaxel‐based therapy of advanced prostate cancer may be improved by combining docetaxel with Aneustat.